Accounting Policy of the Entity Regarding Objects of Fixed Assets, in the IFRS Implementation Context - latsunska О. S. (Statistics of Ukraine, 2016)
The article aims to study the existing methods for analysis of accounting policy and its main components regarding the objects of fixed assets that are subject to disclosure in financial reporting following the requirements of national and international provisions of accounting. The existing theoretical approaches to interpretation of the term “accounting policy” are analyzed, and the conclusion is made that it tends to be classified as a component of accounting organization at a business enterprise, which main purpose is to provide good (transparent) financial reporting to all the user categories. The relation and the hierarchy of the accounting categories “accounting policies” and “accounting estimate” is analyzed. The need to include the category “accounting policy system of a business enterprise” in the accounting terminology and assign it the legal status is substantiated; it is supposed to be a synergetic category encompassing accounting policies and accounting estimates on various objects of accounting, which would allow for eliminating inconsistencies between Ukrainian and international standards of accounting. The key components of accounting policy regarding the objects of fixed assets, which are subject to disclosure in financial reporting, are analyzed by phase of their life cycle. The study is based on the hypothesis that use of the nomenclature of the accounting policy components regarding the objects of fixed assets allows for essential improvement of the information base for enterprise management due to its accounting function, and users’ trust of the financial reporting data. Future studies will be related with interpreting and defining the category “accounting policy system of a business enterprise” and its legal fixing, with due consideration for the existing theoretical studies and international practices.